2009
DOI: 10.1172/jci39590
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of minor histocompatibility antigen–mismatched platelets induces rejection of bone marrow transplants in mice

Abstract: Bone marrow transplantation (BMT) represents a cure for nonmalignant hematological disorders. However, compared with the stringent conditioning regimens used when performing BMT to treat hematological malignancies, the reduced intensity conditioning regimen used in the context of nonmalignant hematological disorders leads to substantially higher rates of BMT rejection, presumably due to an intact immune system. The relevant patient population typically receives transfusion support, often including platelets, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 36 publications
(33 reference statements)
1
53
0
Order By: Relevance
“…However, we have also previously reported that in vivo clearance of mHA expressing targets is variable when measured after platelet transfusion (but prior to BMT) and does not statistically predict BMT rejection (20). In contrast, the current findings and our previous experiments demonstrate that in vivo clearance of donor targets approaches roughly 100% after BMT rejection (20). Combined, these data suggest that LR-PLT transfusions prime recipients for a donor mHA alloresponse that differentiates into to a full effector alloresponse during the BMT.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…However, we have also previously reported that in vivo clearance of mHA expressing targets is variable when measured after platelet transfusion (but prior to BMT) and does not statistically predict BMT rejection (20). In contrast, the current findings and our previous experiments demonstrate that in vivo clearance of donor targets approaches roughly 100% after BMT rejection (20). Combined, these data suggest that LR-PLT transfusions prime recipients for a donor mHA alloresponse that differentiates into to a full effector alloresponse during the BMT.…”
Section: Resultsmentioning
confidence: 83%
“…To test the respective roles of CD4 + and CD8 + T cells in rejection of an MHC-matched BMT in LR-PLT transfused recipients, we made use of our previously described model of MHC-matched:mHA-mismatched BMT (20). In this system, C57BL/6J (H-2 b ) recipients are transfused twice, a week apart, with BALB/c (H-2 d ; MHC- and mHA-mismatched) LR-PLT concentrates (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse models, pretransplant exposure to red cells or platelets can induce rejection of transplanted HLA-compatible BM cells as a result of alloimmunization against mHLAs. 44, 45 Bean et al 46,47 reported that irradiation of blood products could prevent immunization to minor dog leukocyte antigens (minor canine histocompatibility antigen) with reduced risk of graft rejection in canine models of dog leukocyte antigen-compatible related and unrelated donor transplants. However, similar studies of the effect of incompatibility for platelet alloantigens in human HPC transplantation have not yielded similar observations.…”
Section: Do Blood Cells Present Minor Hla Antigens?mentioning
confidence: 99%